Manutenção compulsória de contrato empresarial de longa duração na recuperação judicial - Mendes, Max Magno Ferreira (2022)
The present study intends to demonstrate the compatibility of the Brazilian regulatory system with the compulsory maintenance of long-term business contracts in judicial reorganization. The argumentation will be built in a systematic way from two biases of the national order. The first is the contextualization of compulsory contractual maintenance within the premises of the social function and the economic function of a long-term business contract already under the terms proposed by the Civil Code of 2002 and not by the premises of the Civil Code of 1916. And the second is contextualization of the compulsory extension within the microsystem of the company's law in crisis, more specifically of judicial reorganization. The legal aspect of the compulsory maintenance of a long-term business contract in this dissertation is related to the framing of the principle of private business autonomy, free enterprise and economic freedom at a time of crisis in which the law assumes the inability of the parties to make the overcoming possible the situation of economic and financial difficulty without the intervention of the judge State in enabling a structured negotiation. The argumentation of this dissertation will be based on the analytical and descriptive historical method. This option is justified by the need to delineate the existing connections between the structural change processes of the State and the economic theories that influenced its performance in the regulation of economic activity, more specifically those aimed at minimizing the harmful effects of the extinction of business activity